Human brain development over the early years. (August 2016) - Haartsen, Rianne; Jones, Emily JH; Johnson, Mark H
Graphical abstract: Highlights: Early developmental changes in the brain involve microstructure and connectivity. Resting state networks become tuned and specialized to specific functions. Development of brain structure and function is inter-twined and bi-directional. Infants at risk for autism show deviations in diverse brain measures. Abstract : Recent studies of the structural and functional development of the human brain over the early years have highlighted the rapid development of brain structures and their interconnectivity. Some regional functional specializations emerge within the first months after birth, while others have a more protracted course of development spanning over the first decade or longer. While some anatomical changes enable the emergence of new functions, evidence also points to the importance of resting state oscillations in sculpting neural architecture during development. In atypical development differences in brain structure, function and task-related activity in infancy often precede the emergence of later diagnostic behavioural symptoms.